Aluminum alloy as well as preparation method and application thereof

By controlling the content of elements in aluminum alloys and adjusting the grain structure to form a unique textured aluminum alloy surface, the problem that the existing technology is difficult to meet consumers' personalized needs is solved, and a more market-competitive appearance effect is achieved while maintaining mechanical properties.

CN119913399APending Publication Date: 2025-05-02GUANGDONG HOSHION IND ALUMINUM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411827053.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The existing aluminum alloy surface treatment technology is difficult to meet consumers' demand for unique and personalized appearance, making it difficult for products to stand out in the market.

Method used

By controlling the content of elements and grain size in the aluminum alloy, adjusting its structure, forming a unique texture like a sparkling sea. The specific method includes adjusting the content of trace elements such as Fe, Mn, Cr, Zr, Sc, Er, Ce, La, and regulating the grain structure through steps such as homogenization treatment, deformation heat treatment and tissue manifestation treatment.

Benefits of technology

The unique texture of the aluminum alloy surface is achieved, which enhances the appearance attractiveness while maintaining the mechanical properties and durability of the aluminum alloy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119913399A_ABST
    Figure CN119913399A_ABST
Patent Text Reader

Abstract

The invention discloses an aluminum alloy and a preparation method and application thereof. The aluminum alloy comprises the following components in percentage by mass: 0.06 to 0.28 percent of Fe; 0.24% or less of Mn; less than or equal to 0.15% of Cr; zr < = 0.15%; less than or equal to 0.15% of Sc; less than or equal to 0.15% of Er; 0.24% or less of Ce; 0.24% or less of La; 0.003% to 0.04% of Ti; 0.4% to 5.6% of Mg; 0 to 0.8 percent of Si; 0 to 6.5% of Zn; 0 to 1.1% of Cu; the components of the aluminum alloy at least comprise one of Mn, Cr, Zr, Sc, Er, Ce and La. According to the aluminum alloy disclosed by the invention, the surface presents unique textures like sparkling sea, and the original mechanical property and durability of the aluminum alloy are maintained while the appearance attraction is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of aluminum alloy preparation, and in particular to an aluminum alloy and a preparation method and application thereof. Background Art

[0002] In modern industrial product design, the design of the appearance is not only a means to enhance the attractiveness of the product, but also a key factor affecting its market competitiveness and user experience. Especially in the field of 3C consumer electronics, the combination of product appearance design and its functionality, practicality and performance directly determines the user's choice and the brand's market share. In this field, mobile devices such as mobile phones, tablets, laptops, smart watches, etc. have become an indispensable part of consumers' daily lives. Therefore, the refined treatment of the appearance design of these products, especially the application of aluminum alloy materials, has become an important strategy to enhance user experience and brand image.

[0003] Aluminum alloy materials are widely used in the shells, brackets, frames and other parts of 3C consumer electronic products due to their advantages such as light weight, high strength and corrosion resistance. In these products, aluminum alloy materials not only need to meet the requirements of structural strength and durability, but also take into account the visual effects and feel, becoming a key factor in improving the grade and attractiveness of products. With the continuous improvement of the consumer market's requirements for the appearance design of electronic products, the surface treatment process of aluminum alloys has gradually become a core issue in design. Traditional aluminum alloy surface treatment technologies mainly include high-gloss anodizing and sandblasting anodizing. Although these processes have improved the appearance and durability of aluminum alloy products to a certain extent, they also have some limitations, especially in terms of the uniqueness and personalization of product appearance, and have not yet met the diverse and personalized needs of consumers.

[0004] In the existing technology, sandblasting anodizing is a common surface treatment method for aluminum alloys. Its main process is to apply a layer of oxide film on the surface of the aluminum alloy. This process usually includes first spraying sand or other abrasives onto the surface of the aluminum alloy through compressed air to remove surface defects and form a uniform matte effect, similar to the effect of frosted glass. The surface of the aluminum alloy after sandblasting anodizing has a delicate texture and a comfortable touch, and can effectively improve the corrosion resistance and wear resistance of the material. Therefore, it is widely used in consumer electronic products such as mobile phones and laptops. However, as more and more products adopt sandblasting anodizing, this surface effect has become homogenized, making it difficult to stand out in the market and lacking sufficient personalized characteristics and appeal.

[0005] Another commonly used surface treatment process corresponding to sandblasting anodizing is high-gloss anodizing. High-gloss anodizing technology makes the surface smoother and flatter by mechanically polishing or chemically polishing the surface of the aluminum alloy, and then forms a glossy surface with a mirror effect through anodizing. The surface of the aluminum alloy treated by this process not only has a good visual effect, but also can further improve the surface hardness, enhance its wear resistance and corrosion resistance. The surface of the high-gloss anodized aluminum alloy is smooth, bright, and highly reflective, giving people a high-end and exquisite feeling. Therefore, it is widely used in high-end consumer electronic products. However, similar to sandblasting anodizing, the surface of the aluminum alloy treated with high-gloss anodizing is also difficult to meet the growing personalized needs. The large number of homogenized high-gloss effect products on the market has caused its visual appeal to gradually decline.

[0006] Therefore, on the basis of meeting the practicality and functionality of the product, how to break through the limitations of traditional surface treatment technology and innovate an aluminum alloy appearance effect that is both beautiful and competitive in the market has become an urgent problem to be solved. Summary of the invention

[0007] The object of the present invention is to provide an aluminum alloy having excellent mechanical properties and durability as well as unique texture and attractive appearance.

[0008] The first aspect of the present invention is:

[0009] Provided is an aluminum alloy. The present invention controls the content of elements in the aluminum alloy so that the surface of the aluminum alloy is uniform and delicate, and exhibits a unique texture like a sparkling sea.

[0010] The second aspect of the present invention is:

[0011] Provided is a method for preparing an aluminum alloy. The invention processes the aluminum alloy to adjust the grain size and organizational structure of the appearance surface of the aluminum alloy product, and then performs organizational development treatment to make the aluminum alloy surface show a unique texture like a sparkling sea.

[0012] The third aspect of the present invention is:

[0013] Applications of the aluminum alloy.

[0014] Specifically, the technical solution adopted according to the first aspect of the present invention is:

[0015] An aluminum alloy comprising the following components by mass percentage:

[0016] Fe 0.06~0.28%;

[0017] Mn≤0.24%;

[0018] Cr≤0.15%;

[0019] Zr≤0.15%;

[0020] Sc≤0.15%;

[0021] Er≤0.15%;

[0022] Ce≤0.24%;

[0023] La≤0.24%;

[0024] Ti 0.003~0.04%;

[0025] Mg 0.4%~5.6%;

[0026] Si 0~0.8%;

[0027] Zn 0~6.5%;

[0028] Cu 0~1.1%;

[0029] The components of the aluminum alloy include at least one of the elements Mn, Cr, Zr, Sc, Er, Ce, and La.

[0030] According to the embodiments of the present invention, one of the technical solutions has at least one of the following advantages or beneficial effects:

[0031] The aluminum alloy of the present invention has a unique texture on the surface like the sparkling sea, creating an appearance effect different from the traditional sandblasting anode and high-gloss anode effects, providing more visual changes and appeal. In addition, the aluminum alloy of the present invention maintains the original mechanical properties and durability of the aluminum alloy while improving the appearance appeal.

[0032] The present invention regulates the grain size and organizational structure of the aluminum alloy by limiting the composition and mass ratio of elements in the aluminum alloy, thereby ensuring the generation of unique textures.

[0033] Among them, trace elements such as Mn, Cr, Zr, Sc, Er, Ce, La, and Ti exist in the alloy as insoluble crystalline phases or dispersed phase particles. The presence of a certain amount of these phase particles can increase the recrystallization temperature, inhibit the occurrence of recrystallization, and hinder the growth of recrystallized grains. At the same time, in order to avoid affecting the mechanical properties and corrosion resistance, these trace elements cannot be excessive.

[0034] Among them, Fe is an inevitable impurity element in the original aluminum ingot. Its solubility in solid aluminum is very low, and it usually forms AlFeSi or AlFeSiMn phases with Al, Si, and Mn. These phases exist in the form of needles or spheres. The existence of these needle-shaped or spherical particles can inhibit the occurrence of recrystallization and hinder the growth of recrystallized grains. At the same time, a certain amount of iron phase greatly improves the cutting performance of the material. When the Fe content is too high, mechanical polishing damage is prone to occur, and the anodized color and corrosion resistance of the film layer are reduced, so the Fe content cannot be excessive.

[0035] According to the embodiment of the present invention, the aluminum alloy of the present invention can adjust the contents of Mg, Si, Zn and Cu as needed, so as to adaptively prepare 5 series aluminum alloy, 6 series aluminum alloy or 7 series aluminum alloy, which also shows that the aluminum alloy of the present invention has a high degree of adaptability. The aluminum alloy of the present invention, by limiting the content of trace elements, can make the surface of the aluminum alloy present a unique texture like a sparkling sea, thereby improving the appearance appeal, and the content of the main alloy elements can be adaptively adjusted as needed.

[0036] According to an embodiment of the present invention, when the aluminum alloy of the present invention is adaptively adjusted to a 5-series aluminum alloy, its main alloy element includes Mg, and the mass percentage of Mg in the aluminum alloy is Mg: 4.0% to 5.6%.

[0037] According to an embodiment of the present invention, when the aluminum alloy of the present invention is adaptively adjusted to a 6 series aluminum alloy, its main alloying elements include Mg, Si, and Cu elements, and the mass percentages of the elements in the aluminum alloy are: Mg: 0.4% to 1.0%; Si: 0.2 to 0.8%, Cu: 0.2 to 1.1%.

[0038] According to an embodiment of the present invention, when the aluminum alloy of the present invention is adaptively adjusted to a 7 series aluminum alloy, its main alloying elements include Zn, Mg, and Cu elements, and the mass percentages of the elements in the aluminum alloy are: Mg: 1.5% to 2.5%, Zn: 5.0 to 6.5%, and Cu: 0.2 to 1.1%.

[0039] According to one embodiment of the present invention, the mass percentage of Si element in the aluminum alloy is 0.040-0.450%.

[0040] According to one embodiment of the present invention, the mass percentage of Mg element in the aluminum alloy is 0.820-4.500%.

[0041] According to one embodiment of the present invention, the mass percentage of Zn element in the aluminum alloy is 0.0001-6.000%.

[0042] According to one embodiment of the present invention, the mass percentage of Cu element in the aluminum alloy is 0.030-0.280%.

[0043] According to one embodiment of the present invention, the mass percentage of Fe element in the aluminum alloy is 0.120-0.278%.

[0044] According to one embodiment of the present invention, the mass percentage of Mn element in the aluminum alloy is 0.001-0.240%.

[0045] According to one embodiment of the present invention, the mass percentage of Cr element in the aluminum alloy is 0.001-0.148%.

[0046] According to one embodiment of the present invention, the mass percentage of Zr element in the aluminum alloy is 0.0003-0.150%.

[0047] According to one embodiment of the present invention, the mass percentage of Sc element in the aluminum alloy is 0.0001-0.1480%.

[0048] According to one embodiment of the present invention, the mass percentage of Er element in the aluminum alloy is 0.0001-0.0003%.

[0049] According to one embodiment of the present invention, the mass percentage of Ce element in the aluminum alloy is 0.0001-0.0003%.

[0050] According to one embodiment of the present invention, the mass percentage of La element in the aluminum alloy is 0.0001-0.1950%.

[0051] According to one embodiment of the present invention, the mass percentage of Ti element in the aluminum alloy is 0.003-0.04%.

[0052] According to an embodiment of the present invention, the components of the aluminum alloy of the present invention further include inevitable impurities, and the content of each inevitable impurity is ≤0.05%, and the total amount is ≤0.15%.

[0053] According to an embodiment of the present invention, the composition of the aluminum alloy of the present invention further includes Al element.

[0054] According to one embodiment of the present invention, the average grain intercept of the grains in the aluminum alloy is less than 40 μm. Preferably, the average grain intercept of the grains in the aluminum alloy is 22.3-25.1 μm.

[0055] The average grain intercept of the grains in the aluminum alloy is less than 40 μm, thereby forming a unique grain structure morphology. This grain structure enables the aluminum alloy of the present invention to obtain a differentiated product appearance effect after subsequent surface treatment, while maintaining the original mechanical properties and durability of the aluminum alloy.

[0056] According to one embodiment of the present invention, the average grain intercept of the grains in the aluminum alloy is one of 22.3 μm, 23.8 μm, 24.7 μm, 25 μm, and 25.1 μm.

[0057] According to one embodiment of the present invention, the microstructure of the aluminum alloy is a mixed microstructure of recrystallized and unrecrystallized, and the recrystallization fraction accounts for 20 to 50% in the mixed microstructure. Preferably, the recrystallization fraction accounts for 23 to 42% in the mixed microstructure. The grain structure composed of the average grain intercept and the recrystallization fraction can obtain a differentiated product appearance after subsequent surface treatment, and maintain the original mechanical properties and durability of the aluminum alloy. According to one embodiment of the present invention, the microstructure of the aluminum alloy is a mixed microstructure of recrystallized and unrecrystallized, and the recrystallization fraction accounts for 23%, 28%, 30%, 32, 38% and 42% in the mixed microstructure.

[0058] According to one embodiment of the present invention, the components of the aluminum alloy include at least one of Mn, Cr, Zr, Sc, Er, Ce, La, and Ti, and the Sc equivalent content is 0.04 to 0.16%. The Sc equivalent calculation formula is Sc equivalent = Sc + Zr / 2 + (Cr + Er) / 3 + (Mn + La + Ce) / 5 + Ti / 8. The Sc equivalent reflects the content of trace elements such as Mn, Cr, Zr, Sc, Er, Ce, La, and Ti, and is combined with the strength of each element. When the Sc equivalent is within the range, the element that inhibits recrystallization acts appropriately, and in combination with the preparation method of the present invention, the aluminum alloy of the present invention can obtain a "mixed grain structure with an average intercept of less than 40 μm and a recrystallization volume fraction ratio of 20 to 50%". When the aluminum alloy having such a grain structure is subjected to the tissue development treatment of the present invention, it finally presents the unique texture of the aluminum alloy of the present invention.

[0059] Specifically, the technical solution adopted according to the second aspect of the present invention is:

[0060] A method for preparing the aluminum alloy comprises the following steps:

[0061] S1 melts and casts the raw materials to obtain an aluminum alloy ingot A;

[0062] S2 homogenizes the aluminum alloy ingot A to obtain an aluminum alloy ingot B;

[0063] S3 subjects the aluminum alloy ingot B to deformation heat treatment and structure development treatment to obtain the aluminum alloy.

[0064] According to the embodiments of the present invention, one of the technical solutions has at least one of the following advantages or beneficial effects:

[0065] The preparation method of the aluminum alloy of the present invention can form a pattern with a unique texture on the surface of the aluminum alloy, which not only breaks through the traditional glossy or matte surface effect, but also can provide more changes and appeal visually. Different from the existing sandblasting anode and high-gloss anode effects, this new surface texture effect can bring more personalized characteristics to the aluminum alloy, thereby meeting consumers' demand for a unique and fashionable appearance.

[0066] In addition, this new surface treatment process can also improve the appearance of aluminum alloy while maintaining its original mechanical properties and durability. The aluminum alloy with special texture treatment not only has good corrosion resistance and wear resistance, but also can further enhance the surface strength and scratch resistance by optimizing the texture design.

[0067] According to one embodiment of the present invention, the temperature of the homogenization treatment is 400°C to -600°C.

[0068] According to one embodiment of the present invention, the temperature of the homogenization treatment is 400°C to 530°C.

[0069] According to one embodiment of the present invention, the temperature of the homogenization treatment is 530°C to 550°C.

[0070] According to one embodiment of the present invention, the temperature of the homogenization treatment is 400°C, 530°C or 550°C.

[0071] According to one embodiment of the present invention, the homogenization treatment time is 6 to 10 hours.

[0072] According to one embodiment of the present invention, the homogenization treatment is a two-step treatment, comprising the following steps: first heating to 530-550° C., and then cooling to 400-410° C. Through the two-step treatment, especially the step of controlling the temperature to 400-410° C. after cooling, the dispersion and precipitation of at least one element of Mn, Cr, Zr, Sc, Er, Ce, La, and Ti are further promoted, which can increase the recrystallization temperature, inhibit the occurrence of recrystallization, and hinder the growth of recrystallized grains, thereby obtaining the unique grain structure of the aluminum alloy of the present invention and achieving the appearance effect of the unique texture of the aluminum alloy.

[0073] According to one embodiment of the present invention, the homogenization treatment is a one-step treatment, comprising the following steps: heating to 540° C. and maintaining the temperature for 6 hours.

[0074] According to one embodiment of the present invention, the temperature of the deformation heat treatment is 0.6 to 0.8 times the melting point of the aluminum alloy ingot B. The present invention can control the recrystallization fraction in the aluminum alloy of the present invention to account for 20 to 50% in the mixed microstructure by controlling a relatively low processing temperature. If the deformation heat treatment temperature is too high, the recrystallization fraction will account for too high a proportion; if the deformation heat treatment temperature is too low, the recrystallization fraction will account for too low a proportion, and the 20 to 50% proportion cannot be obtained.

[0075] According to one embodiment of the present invention, during the deformation heat treatment, the heat treatment deformation process time is less than 15 minutes, and the deformation amount is controlled at the same time. That is, the time from the start of the heat deformation to the end of the heat deformation needs to be less than 15 minutes, so as to control the recrystallization fraction in the aluminum alloy of the present invention to account for 20-50% in the mixed organizational structure, thereby ensuring the generation of a unique texture.

[0076] According to one embodiment of the present invention, the deformation heat treatment includes at least one of an extrusion forming process, a hot rolling process and a warm rolling process.

[0077] According to an embodiment of the present invention, the deformation heat treatment includes an extrusion forming process, and the extrusion ratio is 10 to 40. Thus, in the aluminum alloy of the present invention, the recrystallization fraction is further controlled to account for 20 to 50% in the mixed microstructure.

[0078] According to one embodiment of the present invention, during the extrusion forming process, the extrusion temperature is 480-510°C.

[0079] According to one embodiment of the present invention, the hot rolling temperature is 400-420°C, preferably 420°C.

[0080] According to one embodiment of the present invention, the temperature of the warm rolling is 200-250°C, preferably 250°C.

[0081] According to one embodiment of the present invention, the deformation heat treatment includes hot rolling, and the hot rolling thickness deformation is 10-20%, thereby further controlling the recrystallization fraction in the mixed microstructure of the aluminum alloy of the present invention to account for 20-50%.

[0082] According to one embodiment of the present invention, during the deformation heat treatment, when the extrusion ratio or the hot rolling thickness deformation is the upper limit, the solution temperature takes the lower limit.

[0083] According to one embodiment of the present invention, the deformation heat treatment may or may not include artificial aging treatment.

[0084] According to one embodiment of the present invention, the artificial aging treatment has a treatment temperature of 100 to 125° C. and is kept warm for 12 to 24 hours.

[0085] According to one embodiment of the present invention, the artificial aging treatment is performed at a temperature of 125° C. and is kept warm for 24 hours.

[0086] According to one embodiment of the present invention, the deformation amount of the hot rolling treatment is expressed by the hot rolling thickness deformation, and the calculation formula is: δ = (t0-tf) / t0×100%, wherein δ is the rolling thickness deformation, t0 is the thickness of the plate before rolling, and tf is the thickness of the plate after rolling.

[0087] According to one embodiment of the present invention, when the aluminum alloy is an extruded profile, the deformation heat treatment adopts an extrusion forming process.

[0088] According to one embodiment of the present invention, when the aluminum alloy is a rolled plate or strip, the deformation heat treatment adopts hot rolling treatment and warm rolling treatment.

[0089] According to one embodiment of the present invention, the structure revealing treatment is to use an acid solution to perform a revealing treatment on the surface of the aluminum alloy.

[0090] According to one embodiment of the present invention, the acid solution includes at least one of nitric acid, hydrochloric acid, phosphoric acid and hydrofluoric acid.

[0091] According to one embodiment of the present invention, the acid solution is a mixed acid solution of hydrofluoric acid, nitric acid and hydrochloric acid, wherein the mass ratios of hydrofluoric acid, nitric acid, hydrochloric acid and water are 1:5-10:15-20:5--10 respectively.

[0092] According to one embodiment of the present invention, the acid solution is a mixed acid solution of hydrofluoric acid, nitric acid and hydrochloric acid, wherein the mass ratios of hydrofluoric acid, nitric acid, hydrochloric acid and water are 1:5:15:5 respectively.

[0093] According to an embodiment of the present invention, in step S3, after the aluminum alloy ingot B is subjected to deformation heat treatment, it further includes the steps of first performing mechanical polishing treatment and then performing tissue development treatment.

[0094] According to an embodiment of the present invention, in step S3, after the tissue visualization treatment, a further surface treatment step is further included, wherein the surface treatment includes at least one of sandblasting, anodizing and physical vapor deposition.

[0095] Another aspect of the present invention also relates to the application of the aluminum alloy in a mobile phone, a tablet, a computer or a watch, including the aluminum alloy as described in the first embodiment. Since the application adopts all the technical solutions of the aluminum alloy, it has at least all the beneficial effects brought by the technical solutions of the above embodiments.

[0096] According to one embodiment of the present invention, the aluminum alloy prepared by the method of the present invention is not only suitable for common consumer electronic products such as mobile phones, tablets, computers, watches, etc., but can also be expanded to aluminum alloy products in other fields, such as automobiles, home appliances, industrial equipment, etc., providing more innovative possibilities for product design in different industries.

[0097] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0098] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0099] Figure 1 This is the surface morphology of the aluminum alloy prepared in Example 1.

[0100] Figure 2 This is the surface morphology of the aluminum alloy prepared in Example 2.

[0101] Figure 3 This is the surface morphology of the aluminum alloy prepared in Example 3.

[0102] Figure 4 This is the surface morphology of the aluminum alloy prepared in Example 4.

[0103] Figure 5 This is the surface morphology of the aluminum alloy prepared in Example 5.

[0104] Figure 6 This is the surface morphology of the aluminum alloy prepared in Example 6.

[0105] Figure 7 This is the surface morphology of the aluminum alloy prepared in Comparative Example 1.

[0106] Figure 8 This is the surface morphology of the aluminum alloy prepared in Comparative Example 2.

[0107] Fig. 9 This is the surface morphology of the aluminum alloy prepared in Comparative Example 3.

[0108] Fig.10 This is the surface morphology of the aluminum alloy prepared in Comparative Example 4.

[0109] Fig.11 This is the surface morphology of the aluminum alloy prepared in Comparative Example 5.

[0110] Fig.12 This is the surface morphology of the aluminum alloy prepared in Comparative Example 6.

[0111] Fig.13 This is the surface morphology of the aluminum alloy prepared in Comparative Example 7.

[0112] Fig.14 This is the surface morphology of the aluminum alloy prepared in Comparative Example 8.

[0113] Fig.15 Microscope images of the compound morphology on the surface of the aluminum alloy prepared in Examples 1-6.

[0114] Fig.16 This is a microscope image of the compound morphology on the surface of the aluminum alloy prepared in Comparative Example 2.

[0115] Fig.17 This is a microscope image of the compound morphology on the surface of the aluminum alloy prepared in Comparative Example 5. DETAILED DESCRIPTION

[0116] The words "preferred", "more preferred" and the like in the present invention refer to embodiments of the present invention that can provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the description of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention.

[0117] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0118] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of the present invention.

[0119] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0120] Example 1

[0121] An aluminum alloy comprising the following components by mass percentage:

[0122] Si, 0.45%;

[0123] Mg, 0.82%;

[0124] Zn, 0.0001%;

[0125] Cu, 0.03%;

[0126] Fe, 0.278%;

[0127] Mn, 0.238%;

[0128] Zr, 0.15%;

[0129] Ti, 0.015;

[0130] Cr, 0.010%.

[0131] And Sc, Er, Ce, La<0.001%, the balance is Al and inevitable impurities, among the inevitable impurities, the single content is ≤0.05%, and the total amount is ≤0.15%.

[0132] The method for preparing the above aluminum alloy comprises the following steps:

[0133] S1 prepares materials, melts the raw materials, purifies them and then casts them to obtain aluminum alloy ingot A;

[0134] S2 performs homogenization treatment on the aluminum alloy ingot A, wherein the process is heating to 550°C and keeping the temperature for 10 hours, then cooling to 400°C and keeping the temperature for 3 hours, to obtain the aluminum alloy ingot B;

[0135] S3: heating the aluminum alloy ingot B to 510° C. for extrusion, with an extrusion ratio of 18 and a main cylinder forward speed of 3.5 mm / s during extrusion, to obtain an extruded aluminum alloy profile;

[0136] S4 performs aging treatment on the extruded profile at 175°C for 8 hours;

[0137] S5 cuts the extruded profile to obtain an aluminum alloy preform, then performs machining into a specific product shape, and performs mechanical polishing on the aluminum alloy preform after the machining into the specific product shape;

[0138] S6 performs tissue development treatment on the aluminum alloy preform. The tissue development treatment uses a mixed solution in the following ratio: hydrofluoric acid: nitric acid: hydrochloric acid: water = 1:5:15:5 for development. The development time is 60 seconds. After water washing and anodizing operations, an aluminum alloy is obtained.

[0139] Example 2

[0140] The difference between Example 2 and Example 1 is that the mass percentages of elements in the aluminum alloy are different.

[0141] The mass percentages of elements in the aluminum alloy of Example 2 are shown in Table 1.

[0142] Example 3

[0143] The difference between Example 3 and Example 1 is that the mass percentages of elements in the aluminum alloy are different.

[0144] The mass percentages of elements in the aluminum alloy of Example 3 are shown in Table 1.

[0145] Example 4

[0146] The differences between Example 4 and Example 1 are: (1) the mass percentages of elements in the aluminum alloy are different; (2) the preparation methods are different;

[0147] Among them, the mass percentages of elements in the aluminum alloy of Example 4 are shown in Table 1.

[0148] The method for preparing the aluminum alloy of Example 4 comprises the following steps:

[0149] S1 prepares materials, melts the raw materials, purifies them and then casts them to obtain aluminum alloy ingot A;

[0150] S2 performs homogenization treatment on the aluminum alloy ingot A, wherein the process is heating to 530°C and keeping the temperature for 6 hours, then cooling to 410°C and keeping the temperature for 2 hours, to obtain the aluminum alloy ingot B;

[0151] S3: heating the aluminum alloy ingot B to 480° C. for extrusion, with an extrusion ratio of 40 and a main cylinder forward speed of 2.0 mm / s during extrusion, to obtain an extruded aluminum alloy profile;

[0152] S4 performs aging treatment on the extruded profile at 125°C for 24 hours;

[0153] S5 cuts the extruded profile to obtain an aluminum alloy preform, then performs machining into a specific product shape, and performs mechanical polishing on the aluminum alloy preform after the machining into the specific product shape;

[0154] S6 performs tissue development treatment on the aluminum alloy preform. The tissue development treatment uses a mixed solution in the following ratio: hydrofluoric acid: nitric acid: hydrochloric acid: water = 1:5:15:5 for development. The development time is 50 seconds. After water washing and anodizing operations, an aluminum alloy is obtained.

[0155] Example 5

[0156] The difference between Example 5 and Example 4 is that the mass percentages of elements in the aluminum alloy are different.

[0157] Among them, the mass percentages of elements in the aluminum alloy of Example 4 are shown in Table 1.

[0158] Example 6

[0159] The differences between Example 6 and Example 1 are: (1) the mass percentages of elements in the aluminum alloy are different; (2) the preparation methods are different;

[0160] Among them, the mass percentages of elements in the aluminum alloy of Example 6 are shown in Table 1.

[0161] The method for preparing the aluminum alloy of Example 6 comprises the following steps:

[0162] S1 prepares materials, melts the raw materials, purifies them and then casts them to obtain aluminum alloy ingot A;

[0163] S2 performs homogenization treatment on the aluminum alloy ingot A by heating the ingot to 540° C. and keeping the temperature for 6 hours to obtain an aluminum alloy ingot B;

[0164] S3: heating the aluminum alloy ingot B to 250°C, keeping it warm for 5 hours, and then performing multiple warm rolling. The thickness of the product after warm rolling is 11 mm. The warm rolled plate is kept warm at 420°C for 2 hours, and then hot rolled. The thickness of the product after hot rolling is 9.5 mm. The aluminum alloy plate is obtained;

[0165] S4 cuts the extruded profile to obtain an aluminum alloy preform, then performs machining to a specific product shape, and performs a tissue development treatment on the aluminum alloy preform. The tissue development treatment uses a mixed solution in the following proportions: hydrofluoric acid: nitric acid: hydrochloric acid: water = 1:5:15:5 for development, and the development time is 300 seconds. After water washing, sandblasting, and anodizing operations, an aluminum alloy is obtained, wherein 205# zirconium sand is used for sandblasting, and the surface roughness of the workpiece is Ra0.6μm.

[0166] Comparative Example 1

[0167] The preparation method of Comparative Example 1 is the same as that of Example 1. The difference between Comparative Example 1 and Example 1 is that the mass percentage of the elements in the aluminum alloy is different;

[0168] Among them, the mass percentages of elements in the aluminum alloy of Comparative Example 1 are shown in Table 2.

[0169] Comparative Example 2

[0170] The preparation method of Comparative Example 2 is the same as that of Example 1. The difference between Comparative Example 2 and Example 1 is that the mass percentage of the elements in the aluminum alloy is different;

[0171] Among them, the mass percentages of elements in the aluminum alloy of Comparative Example 2 are shown in Table 2.

[0172] Comparative Example 3

[0173] The preparation method of Comparative Example 3 is the same as that of Example 1. The difference between Comparative Example 3 and Example 1 is that the mass percentage of the elements in the aluminum alloy is different;

[0174] Among them, the mass percentages of elements in the aluminum alloy of Comparative Example 3 are shown in Table 2.

[0175] Comparative Example 4

[0176] The preparation method of Comparative Example 4 is the same as that of Example 1. The difference between Comparative Example 4 and Example 1 is that the mass percentage of the elements in the aluminum alloy is different;

[0177] Among them, the mass percentages of elements in the aluminum alloy of Comparative Example 4 are shown in Table 2.

[0178] Comparative Example 5

[0179] The preparation method of Comparative Example 5 is the same as that of Example 4. The difference between Comparative Example 5 and Example 4 is that the mass percentage of the elements in the aluminum alloy is different;

[0180] Among them, the mass percentages of elements in the aluminum alloy of Comparative Example 5 are shown in Table 2.

[0181] Comparative Example 6

[0182] The mass percentages of elements in the aluminum alloy of Comparative Example 6 and Example 1 are the same, and the difference between Comparative Example 6 and Example 1 is that the preparation methods are different.

[0183] The method for preparing the aluminum alloy of Comparative Example 6 comprises the following steps:

[0184] S1 prepares materials, melts the raw materials, purifies them and then casts them to obtain aluminum alloy ingot A;

[0185] S2 performs homogenization treatment on the aluminum alloy ingot A, wherein the process is heating to 550°C and keeping the temperature for 10 hours, then cooling to 400°C and keeping the temperature for 3 hours, to obtain the aluminum alloy ingot B;

[0186] S3: heating the aluminum alloy ingot B to 530° C. for extrusion, with an extrusion ratio of 45 and a main cylinder forward speed of 2 mm / s during extrusion, to obtain an extruded aluminum alloy profile;

[0187] S4 performs aging treatment on the extruded profile at 175°C for 8 hours;

[0188] S5 cuts the extruded profile to obtain an aluminum alloy preform, then performs machining into a specific product shape, and performs mechanical polishing on the aluminum alloy preform after the machining into the specific product shape;

[0189] S6 performs tissue development treatment on the aluminum alloy preform. The tissue development treatment uses a mixed solution in the following ratio: hydrofluoric acid: nitric acid: hydrochloric acid: water = 1:5:15:5 for development. The development time is 60 seconds. After water washing and anodizing operations, an aluminum alloy is obtained.

[0190] Comparative Example 7

[0191] The mass percentages of elements in the aluminum alloy of Comparative Example 7 and Example 1 are the same, and the difference between Comparative Example 7 and Example 1 is that the preparation methods are different.

[0192] The method for preparing the aluminum alloy of Comparative Example 7 comprises the following steps:

[0193] S1 prepares materials, melts the raw materials, purifies them and then casts them to obtain aluminum alloy ingot A;

[0194] S2 performs homogenization treatment on the aluminum alloy ingot A, wherein the temperature is raised to 550° C. and kept at this temperature for 10 hours, and then cooled to below 80° C. within 2 hours, to obtain the aluminum alloy ingot B;

[0195] S3: heating the aluminum alloy ingot B to 510° C. for extrusion, with an extrusion ratio of 18 and a main cylinder forward speed of 3.5 mm / s during extrusion, to obtain an extruded aluminum alloy profile;

[0196] S4 performs aging treatment on the extruded profile at 175°C for 8 hours;

[0197] S5 cuts the extruded profile to obtain an aluminum alloy preform, then performs machining into a specific product shape, and performs mechanical polishing on the aluminum alloy preform after the machining into the specific product shape;

[0198] S6 performs tissue development treatment on the aluminum alloy preform. The tissue development treatment uses a mixed solution in the following ratio: hydrofluoric acid: nitric acid: hydrochloric acid: water = 1:5:15:5 for development. The development time is 60 seconds. After water washing and anodizing operations, an aluminum alloy is obtained.

[0199] Comparative Example 8

[0200] The mass percentages of elements in the aluminum alloy of Comparative Example 8 and Example 1 are the same, and the difference between Comparative Example 8 and Example 1 is that the preparation methods are different.

[0201] The method for preparing the aluminum alloy of Comparative Example 8 comprises the following steps:

[0202] S1 prepares materials, melts the raw materials, purifies them and then casts them to obtain aluminum alloy ingot A;

[0203] S2 performs homogenization treatment on the aluminum alloy ingot A, wherein the process is heating to 550°C and keeping the temperature for 10 hours, then cooling to 400°C and keeping the temperature for 3 hours, to obtain the aluminum alloy ingot B;

[0204] S3: heating the aluminum alloy ingot B to 460° C. for extrusion, with an extrusion ratio of 18 and a main cylinder forward speed of 8 mm / s during extrusion, to obtain an extruded aluminum alloy profile;

[0205] S4 performs aging treatment on the extruded profile at 175°C for 8 hours;

[0206] S5 cuts the extruded profile to obtain an aluminum alloy preform, then performs machining into a specific product shape, and performs mechanical polishing on the aluminum alloy preform after the machining into the specific product shape;

[0207] S6 performs tissue development treatment on the aluminum alloy preform. The tissue development treatment uses a mixed solution with the following ratio: hydrofluoric acid: nitric acid: hydrochloric acid: water = 1:5:15:5 for development. The development time is 60 seconds. Then, it is washed with water and anodized to obtain an aluminum alloy.

[0208] The mass percentages of elements in the aluminum alloy of the embodiment are shown in Table 1.

[0209] Table 1

[0210] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Si% 0.450 0.450 0.450 0.040 0.040 0.040 Mg% 0.820 0.820 0.820 2.000 2.000 4.500 Zn% 0.001 0.001 0.001 6.000 6.000 0.030 Cu% 0.030 0.030 0.030 0.280 0.280 0.100 Fe% 0.278 0.278 0.278 0.065 0.065 0.120 Mn% 0.238 0.001 0.001 0.001 0.001 0.240 Cr% 0.010 0.148 0.001 0.001 0.001 0.080 Zr% 0.150 0.148 0.0003 0.0003 0.0003 0.0020 Sc% 0.0003 0.0003 0.0003 0.0400 0.1480 0.0001 Er% 0.0003 0.0003 0.0003 0.0003 0.0003 0.0001 Ce% 0.0003 0.0003 0.0003 0.0003 0.0003 0.0001 La% 0.0003 0.150 0.1950 0.0001 0.0001 0.0001 Ti% 0.004 0.004 0.004 0.015 0.015 0.004 Sc equivalent 0.127 0.154 0.041 0.043 0.151 0.076

[0211] The mass percentages of elements in the aluminum alloy of the comparative example are shown in Table 2.

[0212] Table 2

[0213]

[0214]

[0215] Performance Testing:

[0216] The aluminum alloys prepared in Examples 1-6 and Comparative Examples 1-8 were subjected to performance tests. The test results are shown in Table 3. The test methods are as follows:

[0217] Reference for characterization of aluminum alloy surface morphology: GBT 3246.1 "Microstructure test methods for deformed aluminum and aluminum alloy products, Part 1 Microstructure test methods".

[0218] The average grain intercept and recrystallization fraction ratio refer to: GB / T 6394 "Method for determination of average grain size of metals".

[0219] Table 3

[0220]

[0221]

[0222] It can be seen from Table 3 that the aluminum alloy prepared by the present invention, by limiting the element content and adopting a specific preparation method, thereby regulating the average grain intercept and recrystallization fraction ratio in the aluminum alloy, ensuring the generation of unique texture, and the surface compounds of the aluminum alloys of Examples 1-6 are finely and evenly distributed, without linear arrangement or clustered arrangement, providing conditions for unique texture (compound arrangement length exceeding 100 μm is defined as linear arrangement, and compound width exceeding 2 μm and length exceeding 10 μm is defined as clustered arrangement).

[0223] Among them, the aluminum alloy of Comparative Example 1 has an Fe content that is too low. Since the Fe element has the effect of inhibiting recrystallization, when the Fe element content is low, the average grain intercept is too large and the recrystallization fraction ratio is too high, resulting in visible spots on the appearance of the aluminum alloy.

[0224] Among them, the aluminum alloy of Comparative Example 2 has an excessively high Fe content. Since the solubility of Fe in solid aluminum is extremely low, it exists as an insoluble primary phase. The high Fe content causes the Fe-stacked iron phase to be arranged linearly. After surface treatment, the linear arrangement area is concave and has a dull appearance.

[0225] Among them, the aluminum alloy of Comparative Example 3 has too low Ti content, resulting in too large average grain intercept and too high recrystallization fraction ratio, resulting in abnormally coarse spots on the appearance. Because Ti plays a role in refining the grains of cast rods during smelting and casting, when Ti is low, the grains of cast rods are abnormally coarse and inherited to the product after hot deformation treatment, resulting in coarse spots on the appearance of the product.

[0226] Among them, the aluminum alloy of Comparative Example 4 has a poor ratio of Sc, Zr, Cr, Er, Mn, La, Ce and Ti elements, which makes the Sc equivalent too large. The Sc equivalent is too large and the ability to inhibit recrystallization is too strong, resulting in a lower recrystallization fraction on the aluminum alloy product. The aluminum alloy products are mostly finer and elongated grains, which makes the grain boundaries longer in the same area of ​​the product, which is reflected in the dull appearance of the aluminum alloy after surface treatment.

[0227] Among them, the aluminum alloy of Comparative Example 5 has too high Ti content. Since the solubility of Ti in solid aluminum is extremely low, it is embedded in the aluminum matrix in the form of insoluble large and long hard particles. The Ti content is too high, causing this area to be concave after surface treatment, resulting in a dull appearance of the aluminum alloy with unevenly distributed concave lines.

[0228] Among them, the aluminum alloy of comparative example 6 has the same mass percentage of elements as the aluminum alloy of embodiment 1, but the preparation method is different from that of embodiment 1. In step S3, comparative example 6 adjusts the extrusion molding parameters, reduces the extrusion temperature, increases the extrusion ratio, and reduces the forward speed of the main cylinder of the extruder during extrusion, relative to embodiment 1, resulting in an excessively large average grain intercept, an excessively high recrystallization fraction ratio, and visible spots on the appearance of the aluminum alloy; due to the larger extrusion ratio, the degree of deformation of the metal during hot extrusion is also greater, the degree of metal deformation is large, the internal energy storage increases, and under certain temperature conditions, the proportion of the recrystallization fraction will also be greater, and the 20-50% recrystallization fraction required by the present invention cannot be achieved in the mixed organizational structure.

[0229] Among them, the aluminum alloy of comparative example 7 has the same mass percentage of elements as that of the aluminum alloy of embodiment 1, but the preparation method of comparative example 7 is different from that of embodiment 1. In comparative example 7, relative to embodiment 1, the homogenization treatment of step S2 is adjusted, and "heating to 550°C and keeping warm for 10 hours, then cooling to 400°C and keeping warm for 3 hours to obtain aluminum alloy ingot B" is adjusted to "heating to 550°C and keeping warm for 10 hours, then cooling to below 80°C for 2 hours to obtain aluminum alloy ingot B", that is, the homogenization treatment of comparative example 7 is a single-stage high-temperature treatment. Under this condition, the Sc equivalent element is not fully precipitated as a high-temperature precipitation phase, or the precipitate is slightly larger, the ability to inhibit recrystallization is reduced, and the recrystallization fraction accounts for a larger proportion, which leads to an excessively large average grain intercept, resulting in an uneven surface of the aluminum alloy, abnormally coarse spots on the outer layer, and a dull inner layer.

[0230] Among them, the aluminum alloy of comparative example 8 has the same mass percentage of elements as the aluminum alloy of embodiment 1, but the preparation method is different from that of embodiment 1. In step S3, comparative example 8 adjusts the extrusion molding parameters, reduces the extrusion temperature, and increases the forward speed of the main cylinder of the extruder during extrusion relative to embodiment 1. Due to the excessively fast extrusion speed, the frictional heat generated by the outer metal layer, the equipment and the mold cannot be dissipated in time in comparative example 8, the outer metal temperature is high, the product recrystallizes and grows into coarse crystals, and the inner layer still has a fibrous crystal structure with a low recrystallization fraction. After surface treatment, the surface of the product is uneven, the outer layer has abnormally coarse spots, and the inner layer is darker.

[0231] The surface morphology of the aluminum alloy prepared in Example 1 is as follows: Figure 1 As shown, Figure 1 (a) is the visual view, from which we can see that the appearance has a special texture like the sparkling sea. Figure 1 (b) is a microscope image with a magnification of x45. Figure 1 (c) is a metallographic microscope image with a magnification of X50. Figure 1(d) in the figure is a metallographic microscope image with a magnification of X100. It can be seen from the figure that the surface is uniform and has no spots.

[0232] The surface morphology of the aluminum alloy prepared in Example 2 is as follows: Figure 2 As shown, Figure 2 (a) is the visual view, from which we can see that the appearance has a special texture like the sparkling sea. Figure 2 (b) is a microscope image with a magnification of x45. Figure 2 (c) is a metallographic microscope image with a magnification of X50. Figure 2 (d) in the figure is a metallographic microscope image with a magnification of X100. It can be seen from the figure that the surface is uniform and has no spots.

[0233] The surface morphology of the aluminum alloy prepared in Example 3 is as follows: Figure 3 As shown, Figure 3 (a) is the visual view, from which we can see that the appearance has a special texture like the sparkling sea. Figure 3 (b) is a microscope image with a magnification of x45. Figure 3 (c) is a metallographic microscope image with a magnification of X50. Figure 3 (d) in the figure is a metallographic microscope image with a magnification of X100. It can be seen from the figure that the surface is uniform and has no spots.

[0234] The surface morphology of the aluminum alloy prepared in Example 4 is as follows: Figure 4 As shown, Figure 4 (a) is the visual view, from which we can see that the appearance has a special texture like the sparkling sea. Figure 4 (b) is a microscope image with a magnification of x45. Figure 4 (c) is a metallographic microscope image with a magnification of X50. Figure 4 (d) in the figure is a metallographic microscope image with a magnification of X100. It can be seen from the figure that the surface is uniform and has no spots.

[0235] The surface morphology of the aluminum alloy prepared in Example 5 is as follows: Figure 5 As shown, Figure 5 (a) is the visual view, from which we can see that the appearance has a special texture like the sparkling sea. Figure 5 (b) is a microscope image with a magnification of x45. Figure 5 (c) is a metallographic microscope image with a magnification of X50. Figure 5 (d) in the figure is a metallographic microscope image with a magnification of X100. It can be seen from the figure that the surface is uniform and has no spots.

[0236] The surface morphology of the aluminum alloy prepared in Example 6 is as follows: Figure 6 As shown, Figure 6 (a) is the visual view, from which we can see that the appearance has a special texture like the sparkling sea. Figure 6 (b) is a microscope image with a magnification of x45. Figure 6 (c) is a metallographic microscope image with a magnification of X50. Figure 6 (d) in the figure is a metallographic microscope image with a magnification of X100. It can be seen from the figure that the surface is uniform and has no spots.

[0237] The surface morphology of the aluminum alloy prepared in Comparative Example 1 is as follows: Figure 7 As shown, Figure 7 (a) is a visual view, from which it can be seen that there are visible spots on the appearance. Figure 7 (b) is a microscope image with a magnification of x45. Figure 7 (c) in the figure is a metallographic microscope picture with a magnification of X100. It can be seen from the picture that there are blocky spots on the surface.

[0238] The surface morphology of the aluminum alloy prepared in Comparative Example 2 is as follows: Figure 8 As shown, Figure 8 (a) is a visual view, from which it can be seen that the appearance is dull and there are unevenly distributed concave lines. Figure 8 (b) is a microscope image with a magnification of x45. Figure 8 (c) is a metallographic microscope image with a magnification of X50. Figure 8 (d) in the figure is a metallographic microscope image with a magnification of X100. It can be seen from the image that there are obvious concave lines on the surface.

[0239] The surface morphology of the aluminum alloy prepared in Comparative Example 3 is as follows: Fig. 9 As shown, Fig. 9 (a) is a visual view, from which it can be seen that the appearance has obvious abnormal and coarse spots. Fig. 9 (b) is a microscope image with a magnification of x45. Fig. 9 (c) in the figure is a metallographic microscope picture with a magnification of X100. It can be seen from the picture that the surface has coarse and blocky spots.

[0240] The surface morphology of the aluminum alloy prepared in Comparative Example 4 is as follows: Fig.10 As shown, Fig.10 (a) is a visual view, from which we can see that the appearance is dull. Fig.10 (b) is a microscope image with a magnification of x45. Fig.10 (c) is a metallographic microscope image with a magnification of X50. Fig.10 (d) in the figure is a metallographic microscope image with a magnification of X100.

[0241] The surface morphology of the aluminum alloy prepared in Comparative Example 5 is as follows: Fig.11 As shown, Fig.11 (a) is a visual view, from which it can be seen that the appearance is dull and there are unevenly distributed concave lines. Fig.11 (b) is a microscope image with a magnification of x45. Fig.10 (c) is a metallographic microscope image with a magnification of X50. Fig.11 (d) in the figure is a metallographic microscope image with a magnification of X100.

[0242] The surface morphology of the aluminum alloy prepared in Comparative Example 6 is as follows: Fig.12 As shown, Fig.12 (a) is the visual view. Fig.12 (b) is a microscope image with a magnification of x45. Fig.12 (c) is a metallographic microscope image with a magnification of X50, from which it can be seen that spots are visible to the naked eye.

[0243] The surface morphology of the aluminum alloy prepared in Comparative Example 7 is as follows: Fig.13 As shown, it can be seen from the picture that its surface is uneven, the outer layer has abnormally coarse spots, and the inner layer is darker.

[0244] The surface morphology of the aluminum alloy prepared in Comparative Example 8 is as follows: Fig.14 As shown, it can be seen from the picture that its surface is uneven, the outer layer has abnormally coarse spots, and the inner layer is darker.

[0245] Microscope images of the compound morphology on the surface of the aluminum alloy prepared in Examples 1-6, such as Fig.15 As shown in the figure, it can be seen that the compound particles on the surface are small and evenly distributed.

[0246] The microscopic image of the compound morphology on the surface of the aluminum alloy prepared in Comparative Example 2 is as follows: Fig.16 As shown in the figure, it can be seen that the compounds (iron phase) on the surface are arranged linearly with a length of more than 300 μm.

[0247] The microscopic image of the compound morphology on the surface of the aluminum alloy prepared in Comparative Example 5 is as follows: Fig.17 As shown in the figure, it can be seen that the titanium particles on the surface are aggregated and embedded in the aluminum matrix, with a width exceeding 2μm and a length exceeding 10μm.

[0248] The above are only embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent transformations made using the contents of the present invention specification, or directly or indirectly applied in related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. An aluminum alloy, characterized in that: Calculated by mass percentage, it includes the following components: Fe 0.06~0.28%; Mn≤0.24%; Cr≤0.15%; Zr≤0.15%; Sc≤0.15%; Er≤0.15%; Ce≤0.24%; La≤0.24%; Ti 0.003~0.04%; Mg 0.4%~5.6%; Si 0~0.8%; Zn 0~6.5%; Cu 0~1.1%; The components of the aluminum alloy include at least one of the elements Mn, Cr, Zr, Sc, Er, Ce, and La.

2. An aluminum alloy according to claim 1, characterized in that: The average grain intercept of the grains in the aluminum alloy is less than 40 μm.

3. The aluminum alloy according to claim 1, characterized in that: The microstructure of the aluminum alloy is a mixed microstructure of recrystallized and non-recrystallized, and the recrystallization fraction accounts for 20-50% of the mixed microstructure.

4. The aluminum alloy according to claim 1, characterized in that: The components of the aluminum alloy include at least one of Mn, Cr, Zr, Sc, Er, Ce, La and Ti, the Sc equivalent content is 0.04-0.16%, and the Sc equivalent calculation formula is Sc equivalent = Sc + Zr / 2 + (Cr + Er) / 3 + (Mn + La + Ce) / 5 + Ti / 8.

5. A method for preparing an aluminum alloy as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: S1 melts and casts the raw materials to obtain an aluminum alloy ingot A; S2 homogenizes the aluminum alloy ingot A to obtain an aluminum alloy ingot B; S3 subjects the aluminum alloy ingot B to deformation heat treatment and structure development treatment to obtain the aluminum alloy.

6. The method according to claim 5, characterized in that: The temperature of the deformation heat treatment is 0.6 to 0.8 times the melting point of the aluminum alloy ingot B.

7. The method according to claim 5, characterized in that: The deformation heat treatment includes at least one of an extrusion forming process, a hot rolling process and a warm rolling process.

8. The method according to claim 7, characterized in that: The deformation heat treatment includes an extrusion forming process, and the extrusion ratio is 10-40.

9. The method according to claim 7, characterized in that: The deformation heat treatment includes hot rolling, and the thickness deformation amount of hot rolling is 10-20%.

10. Use of an aluminum alloy as claimed in any one of claims 1 to 4 in a mobile phone, a tablet, a computer or a watch.